Novel Long‐Chain Diol Phospholipids from Some Bacteria Belonging to the Class Thermomicrobia. Issue 3 (16th December 2014) - Lagutin, Kirill; MacKenzie, Andrew; Houghton, Karen M.; Stott, Matthew B.; Vyssotski, Mikhail
Abstract: Polar lipids of bacteria from the class Thermomicrobia are known to contain long‐chain 1, 2‐diols instead of glycerol, although the nature of polar head groups has not been investigated. We have studied phospholipid classes of two species from the class Thermomicrobia — Sphaerobacter thermophilus and Thermomicrobia sp. WKT50.2. TLC and 31 P‐NMR analysis of polar lipids revealed that both S. thermophilus and Thermomicrobia sp. WKT50.2 contain the same set of four major phospholipid classes. Structures of the novel phospholipids in S. thermophilus were established as 2‐acylalkyldiol‐1‐ O ‐phosphoinositol, 2‐acylalkyldiol‐1‐ O ‐phosphoinositol mannoside, 2‐acylalkyldiol‐1‐ O ‐phospho‐acylmannoside, and 2‐acylalkyldiol‐1‐ O ‐phosphoinositol acylmannoside. To our knowledge, this is the first report of a phospholipid with a mannose directly bound to the phosphate. We also analyzed fatty acids and long‐chain 1, 2‐diols of S. thermophilus and Thermomicrobia sp. WKT50.2 and compared our data with available information for T. roseum . All species share a similar set of fatty acids, with 12‐Me 18:0 being the major fatty acid. The major diol in S . thermophilus was identified as 13‐Me 19:0 (66.2 %). The 21:0 diol was the major component both in Thermomicrobia sp. WKT50.2 (50.6 %) and in T. roseum (56.6 %).